Comparative epidermal morphology of Nigerian species of alchornea (euphorbiaceae) (1999)
The leaf epidermal morphology of the three Nigerian species of Alchornea (Euphorbiaceae) has been studied using light microscopy. Epidermal cells arc irregular with undulate to sinuate anticlinal walls. The abaxial and adaxial walls of A. cor difolia and A.floribunda respectively arc characterized by the presence of knobs on them. All taxa have paracytic stomata. However, while A. cordifolia and A. laxiflora arc amphistomalic, A floribunda is hyposlomatic. Trichomcs arc simple, unicellular and unscriate in A.floribunda and A. laxiflora while stellate trichomcs with two to eight radiating arms are present in A. cordifolia. All taxa except A . laxiflora are entirely smooth on the adaxial surface. An indented dichotomous key based on the features of light microscopy is presented for die identification of die species.